CALCULATION OF CARBON EMISSIONS AND CAP AND TRADE/TAX SCHEMES AT CO-FIRING COAL POWER PLANTS - Agus Noor Sidiq (Universitas Muhammadiyah Semarang, 2022)
The Implementation of co-firing on coal-fired power plants in Indonesia can reduce Greenhouse Gas (GHG) emissions that affect climate change. This reduction in Greenhouse Gas (GHG) emissions has the potential to avoid the carbon tax imposed on carbon-producing industries that exceed the upper limit of carbon emissions. The difference between the Carbon Emission Factor (????????????????2 ) in tons of CO2 e/MWh against the assigned Carbon Cap means the Carbon Economic Value (CEV) owned. CEV can be positive or negative depending on the difference between the results of the Carbon Cap. The opportunity for CEV to be traded depends on the amount of CEV that can be obtained from the co-firing. From this research, it was found that to get a good CEV, the minimum co-firing percentage is 7%. From the calculation results, the lowest value of ????????????????2 (????????????????) that can be achieved in the calculations in this paper is 0.993 tons/MWh at the co-firing percentage of 7%, while the maximum value of ????????????????2 (????????????) was 1.079 tons/MWh at 7% co-firing percentage. From this study, it was also found that the greater the percentage of co-firing used, the lower the value of ????????????????2 (????????????????) while the value of ????????????????2 (????????????) is getting bigger.